Barkham Asylum - Mercado, Yehudi (DC Comics, 2024)
Who’s a good boy?Jester is. Well, he wants to be. Maybe he is? He’s the Joker’s dog so of course he’s funny, but his sense of humor is about to be put to the test. Because when the super-villains of Gotham get thrown into Arkham, their henchpets go to the maximum-security pound known as Barkham Asylum. Being the Clown Prince of Crime’s dog doesn’t win him any friends behind bars, especially after he gets a tough-talking stray cat named Penny tossed into lockup with him. But they’ll have to work together to figure out what the evil Warden Shar Pei’s helper, Dr. Hugo Mange, is up to. And the only way to stop this terrifying team-up is to win the talent show and get visitation with their masters at Arkham on the hill. Because the Joker is sure to help! What could go wrong with that plan? And where does Gotham’s premier playboy Bruce Wayne’s butler Alfred fit in?